Polymer inclusion membrane containing a tripodal diglycolamide (T-DGA): Characterization and sorption isotherm studies. Issue 2 (June 2016) - Mahanty, B.N.; Mohapatra, P.K.; Raut, D.R.; Das, D.K.; Behere, P.G.; Afzal, Md.; Verboom, W.
Highlights: Novel PIMs containing T-DGA ligand with higher extraction efficiency was prepared. The PIMs were characterized by TGA, XRD, SEM, AFM, TIMM, etc. The sorption data were modeled using Lagergren, Ho and Elovich models. The sorption isotherm was also studied and mechanism of uptake proposed. Abstract: Polymer inclusion membranes (PIMs) of the composition, 25.6% T-DGA (tripodal diglycolamide), 53.9% NPOE (2-nitrophenyloctyl ether), and 20.5% CTA (cellulose triacetate) were prepared and characterized using thermogravimetric analysis, X-ray diffraction, scanning electron microscopy (SEM), atomic force microscopy (AFM), and transmission infrared mapping microscopy (TIMM) using Fourier transform infrared (FT-IR) spectroscopy. Uptake of Am 3+ was found to be higher than that of Eu 3+ and >82% uptake of Am 3+ was seen with the PIM of the composition mentioned above. The batch sorption study of Eu 3+ (used as a surrogate of Am 3+ ) by this PIM was investigated in 1 M HNO3 and the data were fitted with different conventional kinetic and isotherm model equations. The sorption followed pseudo-second order (Ho ) kinetic model suggesting a two-step uptake process, a fast chemical reaction followed by a slow diffusion process. The experimental data were best fitted with a three-parameter model, i.e., the Redlich-Peterson isotherm model. A comparison is made with results obtained with T2EHDGA-based PIMs reported earlier.